Primary Compact Cesium Clock (PC3) - (:unkn) unknown (My University, 2025)
Primary Cesium beam Clocks are at the heart of many precise timing or synchronization applications, e.g. in telecommunication networks or for the generation of national or system timescales (e.g. GPS, Galileo). The current industrial products available on the market are relatively bulky instruments with high profile (3U, volume about 30 liters). In this project we investigate on the possibilities to strongly reduce the size of the Cesium clock’s physics package, by developing a new design of the Cesium tube which combines the Cesium atomic beam, surrounding vacuum vessel and a compact microwave cavity. The envisaged compact Cesium clock is expected to open new application possibilities where accuracy or primary clock stability performances are required from a highly compact clock.
Keywords: horloges atomiques; césium